2012
DOI: 10.1002/ejoc.201201099
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Condensation of Amines and Vicinal Diols to Substituted Piperazines

Abstract: A straightforward procedure is described for the synthesis of piperazines from amines and 1,2‐diols. The heterocyclization is catalyzed by [Cp*IrCl2]2 and sodium hydrogen carbonate and can be achieved with either toluene or water as solvent. The transformation does not require any stoichiometric additives and only produces water as the byproduct. The reaction can be performed between a 1,2‐diamine and a 1,2‐diol or by a double condensation between a primary alkylamine and a 1,2‐diol. At least one substituent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…173 Other interesting applications of Ir-based catalyst led to the N-alkylation of carbohydrate alcohols leading to N-substituted aminosugars with potential applications in the biochemical and pharmaceutical fields. 174 Similarly, Fujita et al reported that [Cp*IrCl 2 ] 2 efficiently catalyzed the coupling between different amines and monoalcohols, or even vicinal diols for the synthesis of Nheterocycles, 175,176 whereas a related Ir compound [Cp*IrI 2 ] 2 was also successfully applied in this reaction in a more benign aqueous media and without requiring the use of a base. 159 Besides, the synthesis of N-heterocycles through an intramolecular reaction of amines has also been described to take place in the presence of closely related Ir-based catalysts.…”
Section: Activation Of Alcoholsmentioning
confidence: 99%
“…173 Other interesting applications of Ir-based catalyst led to the N-alkylation of carbohydrate alcohols leading to N-substituted aminosugars with potential applications in the biochemical and pharmaceutical fields. 174 Similarly, Fujita et al reported that [Cp*IrCl 2 ] 2 efficiently catalyzed the coupling between different amines and monoalcohols, or even vicinal diols for the synthesis of Nheterocycles, 175,176 whereas a related Ir compound [Cp*IrI 2 ] 2 was also successfully applied in this reaction in a more benign aqueous media and without requiring the use of a base. 159 Besides, the synthesis of N-heterocycles through an intramolecular reaction of amines has also been described to take place in the presence of closely related Ir-based catalysts.…”
Section: Activation Of Alcoholsmentioning
confidence: 99%
“…Iridium-catalyzed cyclocondensations of vicinal diamines with vicinal diols was reported by Madsen and co-workers. 16 While it may be possible to further optimize the reaction conditions, BH cyclization using complex 1 using the standard conditions is thus far only moderately efficient; 2-methylpiperazine ( 28 ) and tetrahydroquinoxaline 29 are obtained in ca. 40% yield from the reaction of 1,2-propanediol ( 13a ) with the requisite diamine.…”
Section: Resultsmentioning
confidence: 99%
“… 5 For example, the nickel-, 6 iron-, 7 cobalt-, 8 manganese-, 9 silver-, 10 and copper- 11 atalyzed N -alkylation of amines with alcohols via borrowing hydrogen was extensively reported. Besides, the ruthenium 12 and iridium complexes 13 are also employed in this transformation of N -alkylation.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of cyclometalated iridium compounds for N -alkylation of amines with alcohols has been well studied and documented ( Scheme 1 a,b). 13 Recently, we realized the transfer hydrogenation reduction of aldehydes and ketones and the hydroxylation of silane using a series of cyclometalated iridium catalysts, 14 which showed a high catalytic efficiency. Encouraged and inspired by the results of our previous studies, we envisioned whether these cyclometalated iridium complexes can be used for N -alkylation of amines with alcohols via borrowing hydrogen to develop an efficient, mild, and environmentally friendly catalytic methodology.…”
Section: Introductionmentioning
confidence: 99%